Breakthrough infection after COVID-19 vaccination: A threat for Nepal due to SARS-CoV-2 variants circulating in 2nd wave ravaging India (Journal of Patan Academy of Health Sciences, 2021)
After a year of the COVID-19 pandemic, the meta-analysis in Dec 2020 did not support its reinfections. Now it’s clear that not only reinfection following earlier exposure is a reality, but also breakthrough infections after vaccinations have been increasingly reported. A breakthrough infection means that the infection has broken through the protection provided by the vaccine. The course of the disease, strict observation for preventive measures, together with safe vaccines is necessary long-term solutions. The effectiveness of the vaccine, durability of immunity, the role of the virus variants, the incidence and severity of breakthrough infections are the challenges in real life. A breakthrough infection is the detection of SARS-CoV-2 RNA or antigen in the respiratory specimen ≥14 days after inoculation of a vaccine. A breakthrough infection of 0.04 to 13% has been reported in the literature. Nepal began vaccine rollout in late Jan 2021. Nearly 3 million population has been vaccinated by two vaccines, the Covishield (AstraZeneca, from India) and Vero Cell (Sinopharm, China). Only minor ‘Adverse Event Following Immunization’ after the initial vaccine rollout has been reported. There is a lack of reports on the breakthrough infection for these vaccines in the local population. Analysis of the data on breakthrough infection from the vaccine rollouts in Nepal is awaited.